Screening of Evaluation Index and Construction of Evaluation Index System for Mine Ventilation System - Qiu-Ping Bi (MDPI AG, 2021)
The mine ventilation system is an indispensable component to improve coal mining efficiency and ensure the safety of production. Only by clearly grasping the comprehensive evaluation quality of the ventilation system can effective countermeasures be formulated. This paper establishes an evaluation index system for mine ventilation systems by combining a qualitative survey with quantitative research. Specifically, the primary indicators are screened through R-type clustering and the coefficient of variation method. The weight of each index is determined by the entropy weight method. Moreover, the technique for order preference by similarity to ideal solution (TOPSIS) method is used to evaluate the quality of the mine ventilation system. Finally, this evaluation system is used to evaluate the ventilation renovation project in the production mining area of the Sihe mine. The evaluation results verify the effectiveness of the establishment of the mine ventilation evaluation index system and of the evaluation methods.